Taxonomy of the order Mononegavirales: update 2017 - Amarasinghe, Gaya K.; Bào, Yīmíng; Basler, Christopher F.; Bavari, Sina; Beer, Martin; Bejerman, Nicolás; Blasdell, Kim R.; Bochnowski, Alisa; Briese, Thomas; Bukreyev, Alexander; Calisher, Charles H.; Chandran, Kartik; et al. (Archives of virology, 2017)
In 2017, the order Mononegavirales was expanded by the inclusion of a total of 69 novel species. Five new rhabdovirus genera and one new nyamivirus genus were established to harbor 41 of these species, whereas the remaining new species were assigned to already established genera. Furthermore, non-Latinized binomial species names replaced all paramyxovirus and pneumovirus species names, thereby accomplishing application of binomial species names throughout the entire order. This article presents the updated taxonomy of the order Mononegavirales as now accepted by the International Committee on Taxonomy of Viruses (ICTV).